A heartbeat away - Palmer, Michael, 1942-2013; Petkoff, Robert; AudioGO (Firm); Macmillan Audio (Firm) (North Kingstown, R.I. : AudioGO, 2011)
President James Allaire is forced to quarantine everyone in the Capitol when a terrorist group unleashes a deadly, highly contagious virus in the building. Virologist Griffin Rhodes, currently in a maximum security federal prison for alleged terrorist acts, is the only man who can help.
Compact disc.
Title from container.
"Sound Library"--Container.
Release date supplied by publisher.
Recording originally produced by Macmillan Audio, p2011.
In container (17 cm.)
Keywords: United States Capitol (Washington, D.C.) -- Fiction; Virologists -- Fiction; Quarantine -- Fiction; Bioterrorism -- Fiction; Virus diseases -- Fiction; Presidents -- Succession -- United States -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Audiobooks; Suspense fiction